Assessment of The Impact of Apremilast on Levels of IL-17, IL-23, and Lipids in Obese Psoriatic Patient - Saad, Haitham M.; Noaimi, Adil A.; Mahmood, Halla Gh. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Psoriasis is an immune-mediated inflammatory disease with unknown aetiology that may be associated with the defect in proliferation and differentiation of the keratinocytes related to inflammatory cell infiltration. According to published reports, it is universal in occurrence; its prevalence in different populations varies from 0.1% to 11.8%. Receiving Apremilast resulted in a strong reduction in interleukin 17 and interleukin 23, as well as reduced expression of other inflammatory cytokines and improvement of psoriatic lesions. Objectives: This study aimed to assess the impact of Apremilast on levels of IL-17, IL-23, and lipids in obese psoriatic patients. Methods: Thirty obese patients with psoriasis were included in this prospective interventional study to measure serum levels of lipid profile, IL-17, and IL-23, before and after receiving Apremilast treatment. A t-test was used to compare between means. Results: The mean age of the participants was 38 years. The most common age group was 30–40 years. The levels of IL-17 before the administration of Apremilast were 225.55 ± 7.70 pg/mL. After six months of treatment with Apremilast, a statistically significant reduction was seen, with the value decreasing to 183.41 ±2.33 pg/ml. IL-22 levels before the administration of Apremilast were measured to be 76.42 ± 4.03 pg/mL. After six months of treatment with Apremilast, these levels exhibited a non-significant decrease to 67.15 ± 5.40 pg/ml. Modest alterations were noted in the lipid profile. Conclusion: The use of Apremilast is effective in decreasing IL-17 levels, which have pro-inflammatory effects; this leads to improvement in psoriatic lesions. Moreover, receiving Apremilast in obese psoriatic individuals led to a reduction in TG levels and an elevation in HDL-C levels. Additionally, a rise in TC levels and LDL-C was seen.